El juego en el desarrollo integral de niños de 3 a 6 años de la Unidad Educativa Puyango. Periodo 2023-2024 - Jiménez Requelme, Gloria Elizabeth (2024)
The present study focused on investigating the impact of play on the comprehensive development of 3 to 6-year-old children at the Puyango Educational Unit during the period 2023-2024. It explored how play activities influence the physical, cognitive, emotional, and social development of children within this specific age range. To theoretically support the study, a literature review centered on the key variables: play and comprehensive development. The research methodology employed a qualitative, descriptive non-experimental, cross-sectional approach, allowing for a deep and contextual analysis of the results. The total population of the institution consisted of 489 students (244 males and 245 females) and 36 teachers (13 males and 23 females). The selected sample for the study included 17 students and 1 teacher from the initial level 2 parallel "A". Data collection utilized two main instruments: an interview guide with 5 open-ended questions for the teacher, and an observation form with 5 items for the children. The findings revealed significant challenges during play activities, highlighting a relevant issue in this research, prompting a propositive study which concluded with a proposal for teachers aimed at enhancing the teaching- learning process by optimizing play activities. This proposal aimed to address identified challenges and promote a more balanced comprehensive development in young children. Keywords: Play activities, Comprehensive development, Early education, Child play